Lending muscles to archers: Malek Noor plays active role in promoting archery in FT - Sivam, Y.P. (The Star, 2012)
FORMER national bodybuilder Datuk Abdul Malek Mohd Noor, a two-time Mr Universe, will play an active role in the promotion of archery in the Federal Territories.